Keragaman Lumut pada Marga Pandanus di Taman Nasional Ujung Kulon, Banten - Windadri, Florentina Indah (Jurnal Natur Indonesia, 2009)
Ujung Kulon National Park is one of conservation area in Banten Province. A research on bryophytes that grow onpandanus substrat in this area have been done at March to April 2008. The surrounding areas methode used onthis research. In the collections found 9 species usually growth on bark of Pandanus dubius. Two species wasreported as the important species, because one species (Fissidens teysmanianum Doz. & Molk) is endemicspecies in Java and the other (Calymperes cougiense Besch.) as abundant species in Malesia and it is only foundin Polynesia region.